Neural networks for sentence comprehension and production: An ALE‐based meta‐analysis of neuroimaging studies. Issue 8 (28th January 2019) - Walenski, Matthew; Europa, Eduardo; Caplan, David; Thompson, Cynthia K.
Abstract: Comprehending and producing sentences is a complex endeavor requiring the coordinated activity of multiple brain regions. We examined three issues related to the brain networks underlying sentence comprehension and production in healthy individuals: First, which regions are recruited for sentence comprehension and sentence production? Second, are there differences for auditory sentence comprehension vs. visual sentence comprehension? Third, which regions are specifically recruited for the comprehension of syntactically complex sentences? Results from activation likelihood estimation (ALE) analyses (from 45 studies) implicated a sentence comprehension network occupying bilateral frontal and temporal lobe regions. Regions implicated in production (from 15 studies) overlapped with the set of regions associated with sentence comprehension in the left hemisphere, but did not include inferior frontal cortex, and did not extend to the right hemisphere. Modality differences between auditory and visual sentence comprehension were found principally in the temporal lobes. Results from the analysis of complex syntax (from 37 studies) showed engagement of left inferior frontal and posterior temporal regions, as well as the right insula. The involvement of the right hemisphere in the comprehension of these structures has potentially important implications for language treatment and recovery in individuals with agrammatic aphasia following left hemisphere brain damage.